A Thin and Structured Acoustic Metamaterial for Absorption of Airborne Sound - Starkey, Tim (Cranfield University, 2017)
Poster presented at the 2016 Defence and Security Doctoral Symposium.Achieving precise control over the propagation of sound energy has far reaching implications in both airborne and underwater environments. Obtaining a high level of control in the reflection, transmission, and absorption characteristics of sound is a significant challenge in the realisation of the next generation of sonar, acoustic imaging, acoustic cloaking, and sound attenuating devices.Traditionally the control of sound through a medium is governed by the bulk material properties of the fluid or the solid with which the sound is interacting. The bulk modulus and mass density are often the key parameters, but also the limiting factors in many acoustic engineering problems; for instance, it is impossible to absorb low frequency sound with a traditional (bulk) thin lightweight material.One route to overcome these limitations is to design and fabricate bespoke acoustic ‘metamaterials’ to control, guide, or otherwise manipulate the propagation of acoustic energy.  These metamaterials are usually composite materials that comprise structured elements that exhibit periodic or geometric features with physical dimensions that are smaller than the wavelength of sound. The collective behaviour of the structured ensemble can be tuned to produce completely artificial behaviours that would not otherwise be seen using naturally occurring materials. At present there is a rapid expansion in acoustic metamaterial research, with studies demonstrating the potential utility these materials will have in a variety of technological applications.In this poster, I will show how sound absorption by an acoustic metamaterial can be achieved by exploiting the thermos-viscous boundary layer. This boundary layer is created at the interface between air and a solid material due to the ‘non-slip’ boundary condition for sound propagating in the direction tangential to the interface. Our metamaterial comprises a perforated (holey) metal plate separated from a flat surface by a small air gap. The sound attenuation in this structure is strongly dependent on the thickness of the air gap. By using this approach, sound absorbers that are significantly thinner and lighter than conventional sound absorbing panels may be realised.
Keywords: 'Acoustic'; 'Metamaterials'; 'absorbers'; 'DSDS16 poster'; 'DSDS16'; 'Materials Engineering not elsewhere classified'; 'Acoustics and Noise Control (excl. Architectural Acoustics)'